Urine specific gravity as a practical marker for identifying suboptimal fluid intake of runners ~12-hr postexercise - O`Neal, E. K.; Johnson, S. L.; Davis, B. A.; Pribyslavska, V. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
The legitimacy of urine specific gravity (USG) as a stand-alone measure to detect hydration status has recently been challenged. As an alternative to hydration status, the purpose of this study was to determine the diagnostic capability of using the traditional USG marker of >1.020 to detect insufficient recovery fluid consumption with consideration for moderate versus high sweat losses (2.00-2.99 or >3% body mass, respectively). Adequate recovery fluid intake was operationally defined as =100% beverage fluid intake plus food water from one or two meals and a snack. Runners (n = 59) provided 132 samples from five previous investigations in which USG was assessed 10-14 hr after 60-90 min runs in temperate-to-hot environments. Samples were collected after a meal (n = 58) and after waking (n = 74). When sweat losses exceeded 3% body mass (n = 60), the relationship between fluid replacement percentage and USG increased from r = -.55 to -.70. Correct diagnostic decision improved from 66.6 to 83.3%, and receiver operating characteristic area under the curve increased the diagnostic accuracy score from 0.76 to approaching excellent (0.86). Artifacts of significant prerun hyperhydration (eight of 15 samples has USG <1.005) may explain false positive diagnoses, while almost all (84%) cases of false positives were found when sweat losses were <3.0% of body mass. Evidence from this study suggests that euhydrated runners experiencing significant sweat losses who fail to reach adequate recovery fluid intake levels can be identified by USG irrespective of acute meal and fluid intake ~12-hr postrun.